Influences on Infant Feeding: Perceptions of Mother-Father Parent Dyads. Issue 5 (September 2017) - Majee, Wilson; Thullen, Matthew J.; Davis, Alexandra N.; Sethi, Tarunjot K.
Abstract: Purpose: The purpose of this study was to examine interrelational-, organizational-, and community-level influences on how coparents collaborate about infant and toddler feeding. Study Design and Sample: Using qualitative methods, we interviewed mother–father parent dyads to explore the potential influences on infant and toddler feeding. Participants were purposively recruited from two Midwest, rural, university-system pediatric clinics. Thematic analysis was used to code the data. Measures: Mother–father dyadic interviews were conducted using a semistructured interview schedule. Twenty-four mother–father dyads who had a child between the ages of 6 and 36 months were interviewed together. Results: Major themes include interpersonal factors (peer behavior reinforcement, dyad and important others infant feeding conflict, conflict resolution proactiveness), organizational factors (healthcare provider infant-feeding support, workplace flexibility), and community factors (public perception on breastfeeding and social media influence). Clinical Implications: Community-based collaboration can be a platform for mother–father dyads, researchers, public health nurses, and other healthcare providers to proactively create interventions that include opportunity for building coparenting skills and infant-feeding knowledge that promote team management of common early childhood feeding challenges. Abstract : This study includes 24 mother-father parent dyads who were interviewed about potential influences on their infant and toddler feeding practices. Parents offered a number of influencing factors including peer behavior reinforcement, suggestions from grandparents, healthcare provider infant feeding support, workplace flexibility, public perception on breastfeeding, and social media. Nurses can use these data to engage parents in healthy infant and toddler feeding.